Searching for the truth in Keiko applying the sanford meisner approach in portraying actress d in dulaang UP's the dressing room: that which flows away ultimately becomes nostalgia - Madamesila, Marynor Therese G.
This study discusses my creative process applying the Sanford Meisner Approach in building, developing and performing the role of Actress D in Dulaang UP's 40th Theatre Season Ender, The Dressing Room: That Which Flows Away Ultimately Becomes Nostalgia. The Dressing Room was written by Shimizu Kunio,translated into English by John K. Gillespie and adapted by Chiori Miyagawa. In 2016,it was directed by Dr. Alexander Cortez with choreography from Prof. Dexter M. Santos and was shown at the Wilfrido Ma. Guerrero Theater at the University of the Philippines Diliman from April 6- May 24. My study particularly explores my seven chosen Meisner Approach key elements:(1) Reality Doing,(2) Moment-to-moment Acting,(3) Working-off, (4) Actor's Faith, (5) Emotional Preparation, (6) Particularization or As if, and (7) Six Basic Actions and how they were studied and enforced in every step of production process. This study includes a comprehensive documentation of my experience as an actor from the beginning to the very end of the entire production process. It contains articles on Sanford Meisner and his approach, several research materials and analyses on the play and the character, a detailed script breakdown and an in-depth account of how I was able to apply everything I have learned in my performances. This study can serve as a reference to students, actors, theatre practitioners and researchers interested in The Sanford Meisner Approach, the character of Actress D and the play, the Dressing Room: That Which Flows Away Ultimately Becomes Nostalgia.